Agritourism and local products in terms of protection and sustainable development of the Carpathians: a participatory discussion on key issues and challenges (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
The article addresses the development of agritourism and the popularisation of local products as activities that can support the traditional economic functions of the Carpathians (i.e. especially agriculture). The protection of these functions is conducive to combining the preservation of the biodiversity, landscape values, and cultural heritage of the Carpathians with these areas' social and economic development, fulfilling the objectives of the Framework Convention on the Protection and Sustainable Development of the Carpathians. Using a method of participatory discussion (i.e. the World Café), the key challenges of agritourism development and preservation of local products in the Carpathians were identified. Special attention was paid to groups of issues, such as: environmental and social dimensions, agriproducts and food, the development of local products, crafts and small-scale industrial products, cooperation, branding and marketing, and key trends and foresight.